(untitled) (Research, Society and Development, 2024)
Copper (Cu) is one of the metals most used by human beings and its use, in the most diverse applications, goes back ancient times. Presenting a relatively high redox versatility (more than three (3) possible oxidation states with significant stability: Cu(I); Cu(II); Cu(III); and Cu(IV)), it is found mainly in oxidation states +1 (cuprous ion, Cu(I)) and +2 (cupric ion, Cu(II)). Copper (Cu) presents an extremely rich and varied coordination chemistry, starting with the significant differences found in the possible geometries for its respective metallic complexes. Cu(I) has a d10 electronic configuration, while Cu(II) has a d9 configuration and Cu(III) constitutes a d8 configuration. These three (3) distinct electronic configurations represent predispositions to different metal complex geometries (tetrahedral, distorted octahedral and planar quadratic, respectively). It also stands out for being one of the main transition metals in the biological environment, with special action in active sites of highly relevant metalloproteins, such as hemocyanins and blue copper proteins (Cu). The aim of this work is to present an introdutory study on the chemistry of copper (Cu), with special attention to its bioinorganic chemistry, especially the structure-function relationship of copper metalloproteins (Cu), through "Narrative Literature Review". In this way this article presents the chemistry of Copper (Cu), initiating from the fundamental properties of this element, commenting the copper (Cu) characteristics as coordination center, and finalizing with relevant examples of the copper (Cu) action in the biological medium, especially acting as active site of proteins.